(untitled) (Per Musi, 2018)
In 1959, under the direction of conductor Armando Belardi, artistic director of São Paulo’s Gazeta Radio Station, an important milestone was set for the Brazilian music industry: the production works for the recording of the opera Il Guarany by Carlos Gomes at the Municipal Theater of São Paulo, in full and with a Brazilian cast. In this work, we present some historical / social aspects of the production and performance of this opera, starting from documentary sources of the written press and the memory of some protagonists of this process, which brings on the surface the ingenious marketing strategy involving the Radio / Gazeta newspaper, the Municipal Theater of São Paulo and the music industry through the newly created Chantecler label. Until that time, known for the production of Brazilian popular music and, in particular, the country music, Chantecler, by undertaking a project of such size, would open space for its affirmation in the campus of the erudite musical market, thus contributing to the redefinition of a symbolic hierarchization of the musical styles in the field of the Brazilian music industry.